Defects in CrAs and related compounds as a route to half-metallic ferrimagnetism - Galanakis, I.; Ozdogan, K.; Sasioglu, E.; Aktas, B. (Amer Physical Soc, 2006)
Half-metallic ferrimagnetism is crucial for spintronic applications with respect to ferromagnets due to the lower stray fields created by these materials. Studying the effect of defects in CrAs and related transition-metal chalcogenides and pnictides crystallizing in the zinc-blende structure, we reveal that excess of the transition-metal atoms leads to half-metallic ferrimagnetism. The surplus of these atoms are antiferromagnetically coupled to the transition-metal atoms at the perfect lattice sites. The needed condition to achieve half-metallic ferrimagnetism is to prevent the migration of the sp atoms to other sites and atomic swaps.
Keywords: Alloys Mn(2)Vz Z; Pnictides; Al